2018
DOI: 10.3126/jnhrc.v16i2.20305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin Resistant Staphylococcus aureus and Antibiotic Susceptibility Pattern in a Tertiary Hospital in Nepal

Abstract: Background: Methicillin resistant Staphylococcus aureus is a global health challenge nowadays creating problem in antibiotic therapy. This study was aimed to generate resistance pattern of Methicillin resistant Staphylococcus aureus to various antibiotics in order to formulate antibiotic policy for control of Methicillin resistant Staphylococcus aureus in Nepal.Methods: This was a cross-sectional study conducted at the department of Clinical Microbiology, Nepal Medical College Teaching Hospital, from April 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 6 publications
5
12
3
Order By: Relevance
“…Older age groups are more prone to get infected due to decreased host resistance and increased exposure to healthcare settings. In contrast to other studies, we found the highest proportion of MRSA in urine specimens [ 23 , 33 , 34 ]. This may be due to urinary catheterization practice and the colonization by MRSA of indwelling urinary catheters.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Older age groups are more prone to get infected due to decreased host resistance and increased exposure to healthcare settings. In contrast to other studies, we found the highest proportion of MRSA in urine specimens [ 23 , 33 , 34 ]. This may be due to urinary catheterization practice and the colonization by MRSA of indwelling urinary catheters.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies across Asia showed a wide range of methicillin resistance among SA isolates with higher rates in hospital settings (0.7% to 75%) and lower rates in community settings (0% to 48%) [ 21 , 22 , 23 , 24 ]. This is perhaps due to the differences in the study population and geographic locations where the studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Past reports of MRSA from Nepal reported prevalence of 15.4% to 26.0% 17 , 35 and newer studies from various hospitals of Nepal reported higher prevalence: 26% to 69%. 36 , 37 Most of the MRSA related studies conducted in Nepal, used only cefoxitin and/or oxacillin for screening MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…The higher frequency of S. aureus isolation in pus samples compared to other samples has been reported in other studies in Nepal and other parts of the world. 9 - 13 …”
Section: Discussionmentioning
confidence: 99%